Ramifications of Violent Protest on the Environment - Benjamin DAMOAH (Indonesia Strategic Sustainability, 2023)
South Africa has been repeatedly ranked as one of the world's most dangerous countries due to its high level of violence. The country is currently facing a surge of violent protests, which is largely due to a lack of service delivery in communities. The frustration of citizens with the government's unfulfilled promises is a common reason for such protests. University students are also not immune to such violent protests, which often disrupt academic activities. These protests lead to injuries and damage to government buildings, causing harm to both the community and institutions. Additionally, violent protests have disastrous environmental repercussions affecting air quality, aquatic and marine ecosystems. To address this issue, the study suggests that environmental education should be intensified to sensitize the public about the effects of violent protests on the environment. Using the theoretical lens of frustration-aggression theory, the study explored the effects of violent protests in South Africa. The findings highlight the need for urgent action to address the root causes of violent protests, such as inadequate service delivery. The study also emphasizes the importance of raising awareness of the environmental impact of violent protests, and the need for environmental education to be prioritized in the country. By addressing these issues, it is hoped that violent protests will be reduced and a more peaceful and sustainable future can be achieved for South Africa.